The importance of choosing appropriate methods for assessing wild food plant knowledge and use: A case study among the Baka in Cameroon. - Sandrine Gallois; Thomas Heger; Amanda Georganna Henry; Tinde van Andel (PLoS ONE, 2021)
In tropical rainforests, access to and availability of natural resources are vital for the dietary diversity and food security of forest-dwelling societies. In the Congo Basin, these are challenged by the increasing exploitation of forests for bushmeat, commercial hardwood, mining, and large-scale agriculture. In this context, a balanced approach is needed between the pressures from forest exploitation, non-timber forest product trade and the livelihood and dietary behavior of rural communities. While there is a general positive association between tree cover and dietary diversity, the complex biocultural interactions between tropical forest food resources and the communities they sustain are still understudied. This research focuses on the knowledge and use of wild food plants by the forest-dwelling Baka people in southeast Cameroon. By using two different sets of methods, namely ex-situ interviews and in-situ surveys, we collected ethnographic and ethnobotanical data in two Baka settlements and explored the diversity of wild edible plants known, the frequency of their consumption, and potential conflicts between local diet and commercial trade in forest resources. Within a single Baka population, we showed that the in-situ walk-in-the-woods method resulted in more detailed information on wild food plant knowledge and use frequency than the ex-situ methods of freelisting and dietary recalls. Our in-situ method yielded 91 wild edible species, much more than the ex-situ freelisting interviews (38 spp.) and dietary recalls (12 spp.). Our results suggest that studies that are based only on ex-situ interviews may underestimate the importance of wild food plants for local communities. We discuss the limitations and strengths of these different methods for investigating the diversity of wild food plant knowledge and uses. Our analysis shows that future studies on wild food plants would profit from a mixed approach that combines in-situ and ex-situ methods.